2006
DOI: 10.1057/palgrave.ivs.9500113
|View full text |Cite
|
Sign up to set email alerts
|

Human Perception of Structure in Shaded Space-Filling Visualizations

Abstract: Very early in the object recognition process the human visual system extracts shading information. While shading can enhance the visibility of structures, it can have a negative impact on the judgment of sizes of elements in a structure. In certain visualization systems the underlying hierarchical structure is not noticeably explicit, such as in space-filling techniques. We hypothesize that in such cases, shading can make the structure more explicit. In this paper, we report the results of two experiments desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The standard approach in information visualization for the assessment of new techniques is to carry out a task with an existing and a new method, and to measure the time needed and the errors made. [24][25][26][27] Such a comparative evaluation was carried between parallel coordinates and stardinates (a glyph-based technique with multiple dimensions represented on asterisk-like axes). 24 The efficiency and effectiveness of the two visualization methods were compared based on the task completion time, the number of correct answers, the number of hypotheses and on how subjective statements were in agreement with expert views.…”
Section: Comparative Evaluation In Information Visualizationmentioning
confidence: 99%
“…The standard approach in information visualization for the assessment of new techniques is to carry out a task with an existing and a new method, and to measure the time needed and the errors made. [24][25][26][27] Such a comparative evaluation was carried between parallel coordinates and stardinates (a glyph-based technique with multiple dimensions represented on asterisk-like axes). 24 The efficiency and effectiveness of the two visualization methods were compared based on the task completion time, the number of correct answers, the number of hypotheses and on how subjective statements were in agreement with expert views.…”
Section: Comparative Evaluation In Information Visualizationmentioning
confidence: 99%
“…Hue and intensity are examples of color‐based preattentive processing. For example, shading is a preattentive attribute that influences human cognition and recognition (Irani, Slonowsky, and Shajahan‐Human ). In general, experimental studies have demonstrated that individuals recognize and process shaded information more quickly than adjacent, nonshaded entities, objects, or text.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A Shadowed Cushions Treemap [104] is another visual technique designed to provide a better insight into the internal structure of the Treemap. Experiments in [105] have shown that users prefer interacting with this shadowed cushion Treemap and are faster in performing a substructure identification.…”
Section: Visualizing Software Organizationmentioning
confidence: 99%